p97/VCP promotes Cullin‐RING‐ubiquitin‐ligase/proteasome‐dependent degradation of IκBα and the preceding liberation of RelA from ubiquitinated IκBα - Schweitzer, Katrin (J Cell Mol Med, 2015)
Cullin‐RING‐ubiquitin‐ligase (CRL)‐dependent ubiquitination of the nuclear factor kappa B (NF‐κB) inhibitor IκBα and its subsequent degradation by the proteasome usually precede NF‐κB/RelA nuclear activity. Through removal of the CRL‐activating modification of their cullin subunit with the ubiquitin (Ub)‐like modifier NEDD8, the COP9 signalosome (CSN) opposes CRL Ub‐ligase activity. While RelA phosphorylation was observed to mediate NF‐κB activation independent of Ub‐proteasome‐pathway (UPP)‐dependent turnover of IκBα in some studies, a strict requirement of the p97/VCP ATPase for both, IκBα degradation and NF‐κB activation, was reported in others. In this study, we thus aimed to reconcile the mechanism for tumour necrosis factor (TNF)‐induced NF‐κB activation. We found that inducible phosphorylation of RelA is accomplished in an IKK‐complex‐dependent manner within the NF‐κB/RelA‐IκBα‐complex contemporaneous with the phosphorylation of IκBα, and that RelA phosphorylation is not sufficient to dissociate NF‐κB/RelA from IκBα. Subsequent to CRL‐dependent IκBα ubiquitination functional p97/VCP is essentially required for efficient liberation of (phosphorylated) RelA from IκBα, preceding p97/VCP‐promoted timely and efficient degradation of IκBα as well as simultaneous NF‐κB/RelA nuclear translocation. Collectively, our data add new facets to the knowledge about maintenance of IκBα and RelA expression, likely depending on p97/VCP‐supported scheduled basal NF‐κB activity, and the mechanism of TNF‐induced NF‐κB activation.